(untitled) (Research, Society and Development, 2024)
Introduction: The term MIST was first introduced in periodontal surgical procedures in 1995. Minimally invasive surgery aims to reduce operative trauma for the patient compared to the more commonly used and more invasive combined periodontal treatments. Objective: The objective of this research work is to describe the benefits of treating periodontal defects through minimally invasive periodontal surgery. Materials and methods: This research work will be based on 39 scientific articles, it is a bibliographic review, from the year 1999 to the year 2024, articles that contain scientific and up-to-date information related to the effectiveness of minimally invasive periodontal therapy to treat defects. . intraosseous periodontal. Results: MIST, or minimally invasive periodontal surgery, is indicated to treat teeth with deep pockets associated with intrabony defects. The clinical results of this technique are comparable to those of traditional surgical approaches involving larger flaps, with additional benefits such as reduced postoperative pain, improved healing rate, maintenance of soft tissue height, and increased tolerance. by the patient. Conclusion: MIST is an effective option for periodontal treatment in indicated cases. This technique can achieve the same or even better results than conventional techniques, with additional benefits such as greater wound stability, good primary closure, and minimal patient discomfort during and after treatment.